Visual aesthetic quality assessment of urban forests: a conceptual framework - Mundher, Riyadh; Abu Bakar, Shamsul; Al-Helli, Marwah; Gao, Hangyu; Al-Sharaa, Ammar; Mohd Yusof, Mohd Johari; Maulan, Suhardi; Aziz, Azlizam (MDPI, 2022)
Visual aesthetic quality is the visual pleasure level that attracts people and makes them prefer certain areas. Visual aesthetic quality is valued and considered for urban forests but remains challenging. This could be due to a lack of understanding of visual aesthetic quality assessment variables based on visual aesthetic theories. This study supports an integrated conceptual framework based on the result of a systematic literature review study to describe and measure aesthetics that incorporates objective and subjective factors through urban forest visual character and urban forest visual quality. The results include defining and understanding a description of visual aesthetic factors and variables as well as a thorough explanation of visual aesthetic theories to comprehend how to assess the visual aesthetic quality of urban forests. This study agrees with and supports the visual aesthetic theoretical framework, and we believe that due to our shared evolutionary history, humans have a standard set of urban forest visual aesthetic features with preferences that change according to cultural and personal variances. Furthermore, this research provides a foundation of visual aesthetic variables of urban forests that will assist urban forest researchers, urban forest managers, and decision-makers in managing and protecting the visual aesthetics of urban forests.